Un ballo in maschera - Verdi, Giuseppe 1813-1901 (C Major Entertainment GmbH, 2017)
Ten years after stepping down as music director for the Bavarian State Opera, a 'grand Zubin Mehta' (Bayerischer Rundfunk) returned to Munich in March, 2016 to celebrate his 80th birthday conducting Verdi's masterpiece for the first time in a staged production
Title from web page
Wide screen
Interpreten: Piotr Beczala, George Petean, Anja Harteros, Okka von der Damerau, Sofia Fomina, Andrea Borghini, Scott Conner ; orchestra, Bayerisches Staatsorchester ; chorus, Chorus of the Bayerische Staatsoper ; conductor, Zubin Mehta ; stage director, Johannes Erath
Recorded at Bayerische Staatsoper March 3-9, 2016
Keywords: Verdi, Giuseppe -- 1813-1901 -- Un ballo in maschera; Gustav / III / King of Sweden / 1746-1792 / Drama; Filmed operas; Film; Blu-Ray-Disc